ANALISIS HUKUM UNSUR ITIKAD TIDAK BAIK DALAM SENGKETA KEPEMILIKAN MEREK AYAM LEPAAS (STUDI PUTUSAN PENGADILAN NIAGA MEDAN NO. 01/MEREK/2013/PN.NIAGA/MEDAN) - SITI RAHMAH (PREMISE LAW JURNAL, 2016)
Brand dispute in trade is not uncommon because not all brand owners who have been registered are valid owners of the brands. The research used judicial normative method by studying literature materials as secondary data. Based on the analysis, it can be suggested that a brand with legal entity should be registered by the Director or the person who is in charge of it. A brand cannot be registered when the application is based on bad faith. In judge’s decision, related to the Verdict of Medan Commercial Court No. 01/Merek/2013/PN.Niaga/Medan, it is stated that the defendant was in bad faith since he did not include his business partner. Keywords: Bad Faith, Brand Registration, Case of ‘Ayam Lepaas’ Brand